Inclusão dos alunos público alvo da educação especial no ensino médio : concepções e atuação docente - Felicio, Natália Costa de (2017)
Considering the current panorama of the Brazilian school, guided by the assumptions of inclusive education, and the gradual growth in the enrollment of special education students in High School, the present study had as general objective to analyze the conception and performance of high school teachers concerning of special education students. The specific objectives were: a) to verify what teachers think about school inclusion and inclusive pedagogical practice; and, b) analyze how they perceive and reflect on their performance in relation to that student. Based on the qualitative approach, the research was characterized as a case study; being done in the dependencies of a state school of High School located in the central region of a large city of São Paulo state. Twenty-six teachers who worked or had already worked with special education students participated in the study. Data collection was organized in two stages. In the first stage, a questionnaire was applied to the 26 participating teachers, focusing on the conception of school inclusion and teaching performance facing the special education students in High School. In the second stage, among the participants of the study and the avaibility of their timetable, 10 teachers participated in the Focus Group, composed of six meetings, having as central axis the reflection on the pedagogical practice with the student in question; being the data analyzed through the elaboration of categories. The results showed that most of the teachers were in favor of school inclusion, but they pointed out several factors that hinder that process and its performance in relation to that public. In other words, the need for improvement in the physical and organizational structure of the school, specialized professionals to accompany these students, difficulties in pedagogical practice, especially regarding the lack of knowledge about specific topics of Special Education and possible demands for continuing education. In addition, they reflected about the pedagogical practice, the importance of family participation in the school environment, and the need for a management team to discuss with teachers questions regarding school inclusion. Hopefully, the present study will have contributed as a possibility and space to the teachers to reflect on their conceptions and action in relation to the special education students, and that other researches can expand and continue the studies of the area.